Hubungan Peran Tenaga Kesehatan Dengan Kepatuhan Konsumsi Tablet Fe Pada Ibu Hamil Di Puskesmas Silau Laut Kec. Silau Laut Kab. Asahan Tahun 2023 - Irma Agustina; Khairunnisa Situmorang; Isyos Sari Sembiring; Vitalia Hanako Murni Simanjuntak (Jurnal Anestesi, 2024)
In pregnant women, iron plays an important role in fetal growth. This study aims to determine the relationship between the role of health workers and compliance with the consumption of Fe tablets at the Silau Laut Community Health Center, Kec. Sea Glare District. Asahan 2023. This type of research is an analytical survey with a cross-sectional research design, the number of samples used was 32 people obtained using total sampling techniques. The data analysis technique uses chi square. The results obtained in this study were P value = 0.006 < 0.05, which shows that there is a relationship between the role of health workers and compliance with the consumption of Fe tablets. It is recommended that pregnant women increase their compliance in consuming Fe tablets during their pregnancy to maintain the health of themselves and their womb